2021
DOI: 10.1111/jfs.12954
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gas ultrafine bubbles on the potency of chlorine solutions against Listeria monocytogenes biofilms

Abstract: Ultrafine bubble technology is a novel concept in food safety that can improve the potency of antimicrobials against biofilms. This study was conducted to evaluate the impact of gas (air, CO2, or N2) ultrafine bubbles incorporation in 100 and 200 ppm chlorine (Cl2) solutions to inactivate fresh Listeria monocytogenes biofilms on stainless steel. Listeria monocytogenes biofilms were grown on stainless steel coupons through static incubation at 37°C for 72 hr by immersing in L. monocytogenes inoculated brain hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Similarly, supercritical CO 2 was evaluated in combination with PAA against E. coli and L. innocua by Sikin et al (2017), and they concluded that CO 2 acted as a vector for PAA to easily penetrate and inactivate the microbial cells. Similar results were observed in a previous study conducted by Sekhon et al (2021), in which the incorporation of CO 2 UFB in 100 ppm Cl 2 led to significantly greater log reductions in L. monocytogenes biofilms on stainless steel surfaces compared with 100 ppm Cl 2 without UFB.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, supercritical CO 2 was evaluated in combination with PAA against E. coli and L. innocua by Sikin et al (2017), and they concluded that CO 2 acted as a vector for PAA to easily penetrate and inactivate the microbial cells. Similar results were observed in a previous study conducted by Sekhon et al (2021), in which the incorporation of CO 2 UFB in 100 ppm Cl 2 led to significantly greater log reductions in L. monocytogenes biofilms on stainless steel surfaces compared with 100 ppm Cl 2 without UFB.…”
Section: Discussionsupporting
confidence: 91%
“…In previous research, we assessed the impact of gas UFB (referred as microbubbles–nanobubbles) on the efficacy of commonly used AMs in the food industry and demonstrated that the use of CO 2 UFB increased the potency of 200 ppm Cl 2 and 28.4 ppm PAA solutions against Escherichia coli O157: H7 and L. monocytogenes in growth media compared with these AM solutions without UFB (Singh et al, 2021). In another preliminary study, we evaluated the impact of UFB on the efficacy of AMs against fresh L. monocytogenes biofilms on stainless steel surfaces and revealed that the incorporation of air and CO 2 UFB in 100 ppm Cl 2 led to significantly greater log reductions in L. monocytogenes compared with 100 ppm Cl 2 without UFB (Sekhon et al, 2021). After proving the potency of AM in growth media and fresh L. monocytogenes biofilms could be improved by incorporating gas UFB, the next logical step was to evaluate the effectiveness of gas UFB against pathogenic biofilms (such as L. monocytogenes ) on different dairy processing surfaces using more robust experimental design.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we evaluated the impact of gas UFBs (which were referred as micro–nano‐bubbles) on the efficacy of commonly used AMs in the food industry and demonstrated that the use of CO 2 UFBs increased the potency of Cl 2 and PAA solutions against E. coli O157:H7 and L. monocytogenes in growth media compared to these AM solutions without UFBs (Singh et al, 2020). In another previous study, we evaluated the UFBs impact on the efficacy of AMs against L. monocytogenes biofilms on stainless steel surfaces and demonstrated that the incorporation of air and CO 2 UFBs in 100 ppm Cl 2 resulted in significantly greater log reductions in L. monocytogenes biofilms compared to 100 ppm Cl 2 without UFBs (Sekhon, Unger, Singh, Yang, & Michael, 2022). After proving that the potency of antimicrobials in grow media and biofilms could be improved by incorporating UFBs, the next logical step was to evaluate the effectiveness of UFBs in antimicrobials on/in a food matrix.…”
Section: Introductionmentioning
confidence: 98%
“…In a previous study, the combination of CO 2 with calcium hypochlorite was evaluated to eliminate E. coli K-12 during water purification and was determined that CO 2 could penetrate the bacterial cells easily resulting in the improved efficacy of calcium hypochlorite's antimicrobial effect on the bacterial cells(Martirosyan et al, 2012). Similarly,Sekhon et al (2021) examined the incorporation of CO 2 UFB in 100 ppm Cl 2 and observed significantly greater log reductions in L. monocytogenes biofilms on stainlesssteel surfaces compared to 100 ppm Cl 2 without UFB. Unger et al (2023) also confirmed that the incorporation of CO 2 UFB in AM solutions resulted in significantly greater log reductions of fresh and aged L. monocytogenes biofilms on polypropylene, silicone, and stainless-steel surfaces.…”
mentioning
confidence: 99%